2012
DOI: 10.1111/1574-6968.12050
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating effects ofLactobacillusstrains on pathogenicVibrio parahaemolyticus-induced intestinal fluid accumulation in the mouse model

Abstract: The aim of this study was to evaluate the probiotic effects of Lactobacillus strains against Vibrio parahaemolyticus causing gastroenteritis. Six-week-old ICR mice were pretreated with four Lactobacillus strains at three dosages, and then challenged with V. parahaemolyticus TGqx01 (serotype O3:K6). The results showed that V. parahaemolyticus TGqx01 caused severe intestinal fluid accumulation (FA) and villi damage in control mice which were pretreated with phosphate-buffered saline. In contrast, significant all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Most research about the antagonistic effects of other bacterial species on V. parahaemolyticus has focused on applications for aquaculture (Wu et al, 2014; Liu et al, 2015), and most of the strains used cannot be considered probiotics. Studies on the use of probiotics for treating intestinal infection caused by V. parahaemolyticus are rare, and only strains of Lactobacillus have been shown to inhibit V. parahaemolyticus both in vitro and in vivo in mice (Yang et al, 2013). In the current study, we identified a novel commensal B. fragilis strain (Deng et al, 2016) that could reduce cellular damage caused by V. parahaemolyticus and short the colonization period of V. parahaemolyticus in the intestines of mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most research about the antagonistic effects of other bacterial species on V. parahaemolyticus has focused on applications for aquaculture (Wu et al, 2014; Liu et al, 2015), and most of the strains used cannot be considered probiotics. Studies on the use of probiotics for treating intestinal infection caused by V. parahaemolyticus are rare, and only strains of Lactobacillus have been shown to inhibit V. parahaemolyticus both in vitro and in vivo in mice (Yang et al, 2013). In the current study, we identified a novel commensal B. fragilis strain (Deng et al, 2016) that could reduce cellular damage caused by V. parahaemolyticus and short the colonization period of V. parahaemolyticus in the intestines of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although, mice are not natural hosts of V. parahaemolyticus , mouse models are still common used for examining the pathogenesis of V. parahaemolyticus in vivo (Hiyoshi et al, 2010; Yang et al, 2013; Whitaker et al, 2014). In addition to the mouse model, it has been reported that infant rabbits infected with V. parahaemolyticus develop severe diarrhea and enteritis that mimic the main clinical and pathologic manifestations of the disease in humans, so the infant rabbit model is also a good choice for the research of V. parahaemolyticus (Ritchie et al, 2012; Zhou et al, 2013, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…by HT-29 intestinal cells via its antimicrobial activity by producing bacteriocins, lactic acid, and exopolysaccharides. Yang et al 13 also demonstrated that LAB can delay the intestinal fluid accumulation and villus damage caused by V. parahaemolyticus in mice. The authors further reported that strains with stronger adsorption ability are more protective than those with stronger antibacterial ability, indicating that the adsorption capacity is more important 14 .…”
Section: Vibriomentioning
confidence: 97%
“…For example, L. plantarum AS1 show antibacterial activity against several enteropathogens and inhibit V. parahaemolyticus adhesion to the human intestinal cell line HT-29 [ 11 ]. Additionally, mice treated with L. rhamnosus and L. brevis showed a significant reduction in intestinal fluid accumulation and villi damage when animals were challenged with the pathogen [ 12 ].…”
Section: Introductionmentioning
confidence: 99%